2021
DOI: 10.1016/j.nefroe.2022.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in hospitalized patients with COVID-19: A Portuguese cohort

Abstract: Introduction The incidence of acute kidney injury (AKI) in coronavirus disease 2019 (COVID-19) patients ranges from 0.5% to 35% and has been associated with worse prognosis. The purpose of this study was to evaluate the incidence, severity, duration, risk factors and prognosis of AKI in hospitalized patients with COVID-19. Methods We conducted a retrospective single-center analysis of 192 hospitalized COVID-19 patients from March to May of 2020. AKI was diagnosed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(58 reference statements)
2
2
0
Order By: Relevance
“…These findings concur with other reports indicating age as an independent predictor for AKI [14,36,37]. Furthermore, age has also been reported as a risk factor for death in COVID-19 patients [19,38], suggesting that elderly population is at a higher risk of morbidity and mortality, warranting special attention upon admission. In addition, similar to our study cohort, a retrospective study in London demonstrated a three-fold risk of AKI for patients who developed COVID-19 AKI with pre-existing CKD [16].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings concur with other reports indicating age as an independent predictor for AKI [14,36,37]. Furthermore, age has also been reported as a risk factor for death in COVID-19 patients [19,38], suggesting that elderly population is at a higher risk of morbidity and mortality, warranting special attention upon admission. In addition, similar to our study cohort, a retrospective study in London demonstrated a three-fold risk of AKI for patients who developed COVID-19 AKI with pre-existing CKD [16].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the classification of AKI severity is based on KDIGO criteria 2012. We noted that most hospitalized patients who developed AKI predominantly fell into stage 1 (77%), which is in keeping with findings from most other studies indicating stage 1 AKI was the commonest occurrence [14,[19][20][21]. Severe AKI (stage 2 or 3) was more prevailing in critically ill patients who needed intensive care [22,23] and it was associated with higher mortality.…”
Section: Discussionsupporting
confidence: 87%
“…[5] The frequency of acute kidney injury (AKI) in COVID-19 patients goes from 0.5% to 35% and has been related to worse prognosis. [6] TMPRSS2 (trans-membrane serine protease) and ACE2 (Angiotensin-converting enzyme 2) are fundamentally liable for the entry of SARS-COV-2 into various kidney cell types affecting renal function. [7] AKI is common among hospitalized patients with COVID-19, particularly the ones under critical care.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 During the COVID-19 pandemic in the United States, AKI incidence was highly variable. 1,[3][4][5] While the rates of AKI have decreased and even have overall less severity during vaccination, it is still a significant complication. 6,7 However, the molecular pathophysiology of AKI in COVID-19 is unclear.…”
Section: Introductionmentioning
confidence: 99%